Land Valuation and Perceptions of Land Sales Prohibition in Ethiopia - Stein Holden; Sosina Bezu (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2014)
This study investigates attitudes towards legalizing land sales and Willingness to Accept (WTA) sales prices and compensation prices for land among smallholder households in four different areas in the Oromia and SNNP Regions in the southern highlands of Ethiopia. Household panel data from 2007 and 2012 are used. The large majority of the sample prefers land sales to remain illegal, and the resistance to legalizing land sales increased from 2007 to 2012. In the same period, perceived median real land values increased sharply but also exhibit substantial local variation. Land loss aversion is associated with higher land values and less willingness to sell land if land sales were to become legal. The substantial increase in perceived land values, high economic growth and outmigration of youth have yet to persuade the rural population in southern Ethiopia to open the land sales market.
Keywords: P26; Q15; Q24; 330; land sale; land values; compensation values; household perceptions; Southern Ethiopia